Book Review: Fiddler Joe Marble Plays to St. Anne: A Etuaptmumk/Two-Eyed Seeing Pilgrimage by Elder John R. Prosper and Settler Dorothy A. Lander - Pride, Tara; Stilwell, Christie; Gloade, Katie (Healthy Populations Journal, 2023)
While documenting significant Mi’kmaw and settler histories in northeastern Mi’kmaki/Nova Scotia, authors John R. and Dorothy came upon serendipitous signs signalling a much greater mission and opportunity for strengthening Indigenous-settler relationships and spiritual reflection through the lens of St. Anne. Etuaptmumk is the Mi’kmaw word for “multiple perspectives” and asks that we consider, and equally value the strengths of multiple perspectives and ways of knowing. John R. and Dorothy had indeed been guiding their work together through Etuaptmumk from the outset. As researchers who engage in Etuaptmumk in our work, this book proved helpful in guiding our own conversations on ways to strengthen Indigenous-settler relationships and what that looks like “in the real world.”